Making sense out of uncertainty: cognitive strategies in the child custody decision-making process - Mendes, Josimar Antônio de Alcântara; Ormerod, Thomas C. (Frontiers in Psychology, 2024)
Child custody cases post-parental separation entail inherent complexities and uncertainties for legal experts and decision-makers, and are influenced by context factors. This study sheds light on how legal actors (i.e., judges, prosecutors, lawyers, psychologists, and social workers) navigate the uncertainties that arise in such context and, therefore, make their decisions. Based on a reflexive thematic analysis involving 73 participants from Brazil and England, this study reveals cognitive strategies employed by legal actors to comprehend uncertainty and operate in the decision-making context. These strategies encompass heuristics (i.e., selection, evaluation, degrees of freedom, and outsourcing decisions/ resolution) and metacognitive strategies (custodial arrangements, professional practices and ‘best interests of the child’ speech). These results provide a window into the decision-making processes in child custody cases; they offer a comprehensive understanding of the multifaceted sensemaking strategies employed by legal professionals. The results carry substantial implications for informing and improving legal practice in handling complex child custody situations. Furthermore, this study charts new paths for future research by highlighting potential avenues for refining and advancing the strategies employed by legal experts in these cases, especially considering the child’s best interests.